2003
DOI: 10.1364/oe.11.001980
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced visualization of choroidal vessels using ultrahigh resolution ophthalmic OCT at 1050 nm

Abstract: In this article the ability of ultrahigh resolution ophthalmic optical coherence tomography (OCT) to image small choroidal blood vessels below the highly reflective and absorbing retinal pigment epithelium is demonstrated for the first time. A new light source (lambdac= 1050 nm, Deltalambda = 165 nm, Pout= 10 mW), based on a photonic crystal fiber pumped by a compact, self-starting Ti:Al2O3 laser has therefore been developed. Ex-vivo ultrahigh resolution OCT images of freshly excised pig retinas acquired with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 10 publications
3
92
0
3
Order By: Relevance
“…Those wavelengths experience less scattering than the ones at 800 nm, allowing, therefore, for better contrast in deeper tissue layers. 144,145 In ophthalmology, it is of increasing interest to achieve better contrast for choroidal structures that lie below the strongly scattering pigment epithelium [ Fig. 4(d)].…”
Section: Label-free Optical Angiographymentioning
confidence: 99%
“…Those wavelengths experience less scattering than the ones at 800 nm, allowing, therefore, for better contrast in deeper tissue layers. 144,145 In ophthalmology, it is of increasing interest to achieve better contrast for choroidal structures that lie below the strongly scattering pigment epithelium [ Fig. 4(d)].…”
Section: Label-free Optical Angiographymentioning
confidence: 99%
“…However, these long wavelengths are not suited for probing the posterior eye segment in vivo due to strong signal attenuation in the vitreous which mainly consists of water. Hence, the 800 nm range exhibiting very low water absorption is commonly used for retinal imaging [52]. For deep penetration into the subretinal layers, the 1050 nm band provides the best trade-off between these factors [52], while at the same time featuring minimal chromatic dispersion in water [53].…”
Section: Optical Properties Of the Samplementioning
confidence: 99%
“…For this special purpose, the 1050 nm band is interesting, since it exhibits a local minimum of absorption and vanishing chromatic dispersion in water. Since Považay et al demonstrated the potential for deep penetration into the choroid in 2003 [52], a growing number of studies makes use of the 1050 nm range [171,172]. Depending on the diagnostic value of choroid images, 1050 nm OCT may become an additional standard tool for ophthalmology.…”
Section: Developments In Ophthalmic Octmentioning
confidence: 99%
“…This wavelength regime is of interest since the absorption of melanin in RPE decreases with wavelength, therefore imaging with wavelengths greater than 800 nm should allow for better imaging of the choroid below the RPE layer. In a study by Povazay et al, (2003) a Ti:Sapph laser was launched into a PCF generating a supercontinuum source from 400 to 1200 nm which was then passed through long pass filter, resulting in a spectrum with a 165 nm bandwidth centered around 1050 nm . OCT images of ex-vivo pig retina were acquired and also compared with OCT images using a 165 nm bandwidth Ti:Sapph laser at 800 nm .…”
Section: Pcf Based Sourcesmentioning
confidence: 99%